High-yielding nitrate transporter cultivars also mitigate methane and nitrous oxide emissions in paddy - Iqbal, Muhammad Faseeh; Zhang, Yong; Kong, Pulin; Wang, Yulong; Cao, Kaixun; Zhao, Limei; Xiao, Xin; Fan, Xiaorong (Frontiers in Plant Science, 2023)
Development of high yield rice varieties is critical to ensuring global food security. However, the emission of greenhouse gases (GHG) such as Methane (CH4) and Nitrogen oxide (N2O) from paddy fields threatens environmental sustainability. In this study, we selected overexpressed high-affinity nitrate transporters (NRT2.3 along with their partner protein NAR2.1) cultivars, which are effective nitrogen use efficient transgenic lines pOsNAR2.1: OsNAR2.1 (Ox2) and p35S:OsNRT2.3b (O8). We used high (270 kg N/ha) and low (90 kg N/ha) nitrogen (N) fertilizers in paddy fields to evaluate morphophysiological traits, including GHG emission. We found that Ox2 and O8 reduced CH4 emissions by 40% and 60%, respectively, compared to their WT. During growth stages, there was no consistent N2O discharge pattern between WT and transgenics (Ox2, O8) in low and high N application. However, total cumulative N2O in a cropping season reduced in O8 and increased in Ox2 cultivars, compared to WT. Root aerenchyma formation reduced by 30-60 % in transgenic lines. Methanogens like mcrA in low and high N were also reduced by up to 50% from rhizosphere of Ox2 and O8. However, the nitrifying bacterial population such as nosZ reduced in both transgenics significantly, but nirK and nirS did not show a consistent variation. The high yield of transgenic rice with limited aerenchyma mitigates the discharge of CH4 and N2O by reducing root exudates that provide substrates for GHG. Our results improve understanding for breeders to serve the purpose of sustainable development.